Pengaruh keselesaan ke tempat kerja terhadap kualiti hidup penduduk bandar di Mukim Kajang, Selangor. - Haryati Bt. Shafii,; Sharifah Meryam Shareh Musa, (Universiti Kebangsaan Malaysia, 2010)
Comfortable travel to workplace is important in determining the overall societal quality of life. This study has identified that comfortable travel to workplace can contribute to good quality of life. Therefore, comfortable travel to workplace should be considered when assessing urban quality of life. The research issue is uncomfortable travel to the workplace will affect the quality of life. The objective of the study is to look into the perception of the urban residents’ regarding comfortable travel to the workplace. The study was conducted in Kajang town and Bandar Baru Bangi. Questionnaire was administered among 700 respondents who were randomly sampled. The data gathered were analysed using the SPSS. The findings show that 112 respondents work in Kajang town, 105 work in Bandar Baru Bangi, 36 respondents work at Universiti Kebangsaan Malaysia and 26 work in Serdang, while 135 respondents work outside of the study areas. Analysis of relations between distance of workplace from home shows chi square value of 89.329 with 0.05 (p=0.000) level of significance, while the relations of distance of home from workplace with time spent in the traffic jam shows the chi square value of 227.568 with 0.05 (p=0.000) level of significance. A total of 208 respondents is found to be emotionally affected while in the traffic jam, while 150 said that they could still remain calm. A total of 359 respondents stated that it is not comfortable travelling to the workplace when there is traffic jams. It can be concluded that the study of the state of comfort while travelling to the workplace should be used as an indicator of urban quality of life based on the conflicts that the residents experience while on their way to work.